‘Down But Not Out’: critical insights in traditional Shona metaphysics - Viriri, Advice; Mungwini, Pascah (The Journal of Pan African Studies, 2016)
The paper provides a corrective to the Western gaze that modern medicine; science and Christianity are familiar parts of Western imagination. It shows the beauty of African indigenous science, medicine and worship. Colonialism transformed most African parts as a way of “modernizing traditional political, economic and social practices” as many scholars think. The paper is concerned with the socio-political and cultural dimensions of the new hegemonic tendencies in the world’s global affairs, which pose serious challenges to African social sciences.It further discusses how the Shona perceive African metaphysics in the face of modernity global challenges and how they represent the interface of the three traditions namely: science, Christianity and African traditional culture. The Shona people being Africans represent the voice of Africans as a whole and Shona culture in particular. The paper brings out how Shona cultural beliefs specifically those that are metaphysical have demonstrated their resilience in the face of demonization and the onslaught from the West. This refraction of the new hegemonism into African culture and social sciences “still bears the methodological and epistemological hallmarks of the hegemonic dynamics” of the African colonial era that characterizes and continues to shape the discourses about Africa. The paper seeks to resist, dismantle and critique the inherited colonial social science research legacies, which have injured African social scientists’ consciousness.